Hindbrain morphometry and choroid plexus position in differential diagnosis of posterior fossa cystic malformations. (5th August 2019) - Paladini, D.; Donarini, G.; Parodi, S.; Volpe, G.; Sglavo, G.; Fulcheri, E.
ABSTRACT: Objective: To assess the differential diagnostic significance of a series of quantitative and qualitative variables of the cerebellar vermis in fetuses with posterior fossa cystic malformation, including Dandy–Walker malformation (DWM), vermian hypoplasia (VH) and Blake's pouch cyst (BPC). Methods: This was a retrospective study of confirmed cases of DWM, VH and BPC, diagnosed at the Fetal Medicine and Surgery Unit of the Federico II University between January 2005 and June 2013 or the Fetal Medicine and Surgery Unit of G. Gaslini Hospital between July 2013 and September 2017. All included cases had good‐quality three‐dimensional (3D) volume datasets of the posterior fossa, acquired by transvaginal ultrasound through the posterior fontanelle. The midsagittal view of the posterior fossa was the reference view for the study. We assessed brainstem–tentorium angle and brainstem–vermis angle (BVA), as well as craniocaudal (CCVD) and anteroposterior (APVD) vermian diameters and vermian area (VA), which were normalized by biparietal diameter (BPD) to take into account gestational age (CCVD/BPD × 100, APVD/BPD × 100 and VA/BPD × 100, respectively). Finally, the position of the fourth ventricular choroid plexus (4VCP) was defined as normal ('up') or abnormal ('down'), relative to the roof/cyst inlet of the fourth ventricle. Results: We analyzed 67 fetuses with posterior fossa malformations (24 cases of DWM, 13 of VH and 30 of BPC). The mean gestational age at diagnosis was 23.6 weeks. Regardless of gestational age, the BVA differed significantly between the three groups, and the VA/BPD was able to differentiate between VH and BPC. In differentiating between VH and BPC, the greatest areas under the receiver–operating characteristics curve were those for VA/BPD ratio. The 4VCP position was down in all cases of DWM and VH, while it was up in all cases of BPC. Conclusions: Our data support the concept that VA/BPD ratio and 4VCP position may be used to differentiate between DWM, VH and BPC in the fetus. In our series, the position of the 4VCP had the highest accuracy, but a larger number of VH cases should be evaluated to confirm that an up position of the 4VCP indicates BPC while a down position indicates DWM or VH. Copyright © 2018 ISUOG. Published by John Wiley & Sons Ltd.